The Role of Digital Technology in Sustainability Accounting: Findings from Pharmaceutical Companies in Indonesia - Laurent, Agnes Fanny; Wahono, Agung Tri; Ahmad, Ardian; Leasa, Merlisye; Zega, Yosua; Ramadhan, Yanuar (International Journal of Economics Development Research (IJEDR), 2024)
This study aims to explore the role of digital technology in sustainability accounting practices in the pharmaceutical industry in Indonesia. The use of technologies such as big data, artificial intelligence (AI), blockchain, and the Internet of Things (IoT) has enabled pharmaceutical companies to improve operational efficiency and transparency of sustainability reporting. This study also identified challenges faced by pharmaceutical companies, such as regulatory uncertainty, technology implementation costs, and data security issues. This research uses a Systematic Literature Review (SLR) approach to collect and analyse evidence from relevant studies. The results show that digital technology can improve the accuracy of sustainability reporting, reduce environmental impacts, and increase public trust in pharmaceutical companies. The findings support the need for investment in digital technology as part of a long-term sustainability strategy in the pharmaceutical sector.